IDEOLOGICAL BASES OF RUSSIA AND TURKEY POLICIES - Yermekbayev Adilbek Alpysbayevich; Absattarov Galymzhan Raushanbekovich; Williams Joseph (Scientific Journal of Pedagogy and Economics, 2019)
This article examines the issues of national archetypes in the formation of foreign policy, the image of the ruler and the mission of the state. Russia and Turkey position themselves today as countries seeking to challenge the US championship in the world. Both countries have a rich history and ideologically justify their right to lead. In the study of the statehood of Turkey and Russia, an important role was played by the political ideologies that formed the mental image. Russia’s desire to dominate the Balkans, the Middle East, comes from the idea of "Moscow-Third Rome", and the modern ideology of Turkey "Neo-Ottomanism" is a bright continuation of the policy of the Ottoman Empire.